COVID-19 related risk factors and their association with non-syndromic orofacial clefts in five Arab countries: a case-control study - Heba Jafar Sabbagh; Rana A. Alamoudi; Mohammad Zeinalddin; Taimoor Al Bulushi; Ola B. Al-Batayneh; Mamdouh A. AboulHassan; Mohamed Koraitim; Maryam Quritum; Buthaina Almuqbali; Sultan Musaad Alghamdi; Shaimaa Mohsen Refahee; Lateefa Alkharafi; et al. (BMC, 2023)
Abstract Background The environmental etiology of non-syndromic orofacial clefts (NSOFCs) is still under research. The aim of this case-control study is to assess COVID-19 associated factors that may be related to the risk of NSOFC in five Arab countries. These factors include COVID-19 infection, COVID-19 symptoms, family member or friends infected with COVID-19, stress, smoking, socioeconomic status and fear of COVID-19. Methods The study took place in governmental hospitals in five Arab countries from November 2020 to November 2021. Controls are matched in the month of delivery and site of recruitment. A clinical examination was carried out using LASHAL classification. Maternal exposure to medication, illnesses, supplementation, COVID-19 infection during their pregestation and 1st trimester periods were evaluated using a validated questionnaire. Maternal exposure to stress was assessed using the Life Events scale, fear of covid-19 scale, family member or friend affected with covid-19 infection, pregnancy planning and threatened abortion. Results The study recruited 1135 infants (386 NSOFC and 749 controls). Living in urban areas, maternal exposure to medications 3-months pregestation, maternal exposure to any of the prenatal life events and maternal fear of COVID-19 significantly increased the risk of having a child with NSOFC. On the other hand, mothers exposed to supplementation 3-months pregestation, mothers suspected of having COVID-19 infection, family members or friends testing positive with COVID-19 significantly decreased the risk of having a child with NSOFC. Conclusions This study suggests that NSOFC may be associated with maternal exposure to lifetime stress and COVID-19 fear in particular, with no direct effect of the COVID-19 infection itself. This highlights the importance of providing psychological support for expecting mothers during stressful events that affect populations such as the COVID-19 pandemic, in addition to the usual antenatal care.